Antenna Solution For Software Definable Radios - Ooi , Soo Liam (2005)
The Two-way Radios are essential means of wireless communications for both business and mission critical applications. The mission critical applications include the FIre and rescue departments, as well as the public safety personnel. The advancement in RF circuit technology has enabled the development of transceiver operating in multiple bands frequencies. These multi band radios will eventually evolved into what is called the "Software Definable Radios", which the mode of operations, frequency bands and type of application are easily reconfiqured by using the embedded software on the transceivers. This research project explores the technologies to complement the development of software-definable radios by providing multiple band antennas as well as GPS antenna solutions.